2006
DOI: 10.1016/j.joca.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on diffraction enhanced radiographic imaging for a canine model of cartilage damage

Abstract: The present study is the first study for the efficacy of DEI for cartilage lesions in an animal joint, from very early signs through erosion down to subchondral bone, representing the spectrum of cartilage changes occurring in human osteoarthritis (OA). Here we show that DEI allows the visualization of cartilage lesions in intact canine knee joints with good accuracy. Hence, DEI may be applicable for following joint degeneration in animal models of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The capacity of DEI to simultaneously visualize soft and mineralized tissues has obvious applications in the area of joint disease [10][11][12][13][14][15] and efforts are underway at BMIT to develop animal models of arthritic disease that will capitalize on this capability. DEI has also proven effective for bone imaging [16] and it has been frequently reported that DEI produces unique contrast visualization of trabecular bone architecture [17][18][19][20][21][22].…”
Section: Application Of Dei To Musculoskeletal Tissuesmentioning
confidence: 99%
“…The capacity of DEI to simultaneously visualize soft and mineralized tissues has obvious applications in the area of joint disease [10][11][12][13][14][15] and efforts are underway at BMIT to develop animal models of arthritic disease that will capitalize on this capability. DEI has also proven effective for bone imaging [16] and it has been frequently reported that DEI produces unique contrast visualization of trabecular bone architecture [17][18][19][20][21][22].…”
Section: Application Of Dei To Musculoskeletal Tissuesmentioning
confidence: 99%
“…10 In-line phase contrast imaging (PCI) 11 is one SR X-ray imaging method based on similar, but simpler than DEI, principles and, thus, offers easier imaging modality. Due to its simplicity and ability to visualize microstructural details in various biological tissues and TE scaffolds, 12,13 PCI has been commonly used in TE.…”
Section: Introductionmentioning
confidence: 99%
“…Although developments are currently underway for nonsynchrotron‐based DEI systems, which use conventional X‐ray tubes, the images garnered with synchrotron X‐rays will always be held as the gold standard. Studies have been previously carried out on the efficacy of using DEI and phase‐contrast analyzer‐based imaging for the detection of cartilage lesions on disarticulated specimens, both with synchrotron (Li et al, ; Muehleman et al, ; Coan et al, 2010a,b) and nonsynchrotron X‐rays (Muehleman et al, b, ). DEI has even been studied for the evaluation of orthopedic implant integration into bone (Wagner et al, ), and a similarly based analyzer system using phase contrast has gone as far as the longitudinal in vivo imaging of guinea pigs for detection of osteoarthritic lesions (Coan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…An area in which DEI has been particularly focused has been in the imaging of the cartilage and bone changes characteristic of osteoarthritis (OA) (Majumdar et al, 2004;Muehleman et al, 2006Muehleman et al, , 2009aMuehleman et al, ,b, 2010. The diagnosis of OA may be made as a patient begins to feel pain in the affected joint.…”
Section: Introductionmentioning
confidence: 99%